Biochemical Hyperthyroidism in a Newborn Baby Caused by Assay Interaction from Biotin Intake. Issue 3 (12th September 2016) - Bülow Pedersen, Inge; Laurberg, Peter
Abstract : We describe a case of biochemical neonatal thyrotoxicosis caused by biotin supplementation. Biotin may interact with thyroid function testing to imitate thyrotoxicosis with low thyroid-stimulating hormone and elevated triiodothyronine and thyroxine levels.